Pengaruh Pengetahuan dan Kepatuhan Ibu Hamil Minum Tablet Tambah Darah di Desa Selulung Kabupaten Bangli - Anny Eka Pratiwi; Sri Ratna Dewi; Tangking Widarsa; I Wayan Darwata (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Anemia in pregnant women is one of the contributing factors to stunting in toddlers. The consumption of iron (Fe) tablets by pregnant women requires supervision from family members to support the success of the stunting reduction program in Bangli Regency. Iron tablet intervention in pregnant women has been proven to reduce the risk of complications, lower the incidence of low birth weight in infants, and decrease maternal mortality during childbirth. This study used a cross-sectional survey design, involving 48 pregnant women. Data collection was conducted using total sampling during the period from January 2024 to January 2025 at Kintamani IV Public Health Center. Bivariate data analysis was carried out using the chi-square test. The results of the study showed that 68% of pregnant women experienced mild anemia. Most pregnancies were in the third trimester (39%), and 43% of the participants were in their first pregnancy. The majority of the pregnant women had good knowledge levels. There was a significant relationship between pregnant women’s knowledge and their adherence to consuming iron tablets, with a p-value of 0.019. The odds ratio (OR = 5.014) indicated that pregnant women with good knowledge were five times more likely to adhere to iron tablet consumption compared to those with limited knowledge. Support and monitoring of the nutritional status of pregnant women are essential to reduce the incidence of low birth weight and stunting among toddlers in Selulung Village, Kintamani District.